2019
DOI: 10.1088/1361-648x/aafde0
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of crystallinity at a well-defined molecular interface of epitaxial C60 on the single crystal rubrene

Abstract: Uniform and well-defined interfaces are required for clarification of fundamental processes at internal interfaces between donor and acceptor molecules constituting organic optoelectronic devices. In this study, evolution of a well-ordered molecular interface, epitaxially grown C 60 on the single crystal rubrene (C 42 H 28 ) surface, was accurately investigated by grazing incidence x-ray diffraction (GIXD) techniques. Contrasting to the case of C 60 on the single crystal pentacene forming uniquely aligned epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 59 publications
(70 reference statements)
1
16
0
Order By: Relevance
“…On the other hand, structural analyses have disclosed well-defined assembly of several organic semiconductor molecules via heteroepitaxial growth on molecular single crystal substrates. [243][244][245][246][247][248][249][250] For instance, it was demonstrated by means of surface X-ray diffraction works that n-type semiconductor molecules of C 60 245 and perfluoropentacene (PFP; C 22 F 14 ) 250 form uniquely oriented crystallites on the single crystal surface of pentacene, and the mean size of these epitaxial crystallites reaches the 100 nm order. 246,248 Before closing this article, photoemission analyses conducted on these well-defined molecular-molecular heterointerfaces built on the Pn-SC will be summarized in the following paragraphs.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, structural analyses have disclosed well-defined assembly of several organic semiconductor molecules via heteroepitaxial growth on molecular single crystal substrates. [243][244][245][246][247][248][249][250] For instance, it was demonstrated by means of surface X-ray diffraction works that n-type semiconductor molecules of C 60 245 and perfluoropentacene (PFP; C 22 F 14 ) 250 form uniquely oriented crystallites on the single crystal surface of pentacene, and the mean size of these epitaxial crystallites reaches the 100 nm order. 246,248 Before closing this article, photoemission analyses conducted on these well-defined molecular-molecular heterointerfaces built on the Pn-SC will be summarized in the following paragraphs.…”
Section: Resultsmentioning
confidence: 99%
“…Those widths correspond to in-plane mean crystallite sizes of 0.12 and 0.16 μm, respectively, which are already comparable to or even greater than those for RT-grown epitaxial C 60 on the RubSC(100) surface. 19 Furthermore, the FWHM of the sharpest component (0.0016 Å –1 ) corresponds to an in-plane mean crystallite size of 0.40 μm, which was 3 times greater than the case of C 60 /RubSC. The present results strongly suggest that minimization of the lattice mismatch at molecular junctions is also a decisive factor for the crystal quality even for the molecular semiconductors as van der Waals condensates.…”
mentioning
confidence: 84%
“…Indeed, a number of molecular species have been reported to exhibit mobility exceeding that of amorphous silicon in single-crystalline field-effect transistor devices composed of these materials. In the case of optoelectronic devices such as organic photovoltaics, conventional architectures are composed of p-type (donor) and n-type (acceptor) materials of disordered condensates, , and thus making use of the highly efficient charge carrier transport of single-crystalline structures may offer another possible concept to improve the device performance. In this context, epitaxial growth of organic semiconductors is a reasonable approach for obtaining crystalline p–n junctions through self-assembly. In previous studies, highly ordered heteroepitaxial interfaces of uniformly aligned n-type molecular materials formed on single crystals of p-type organic semiconductors have been attained. Moreover, it has been confirmed that single-crystalline thin films with extremely good crystallinity can be obtained by homoepitaxy, where molecules are deposited on single-crystal substrates of the same molecular species. This methodology enables the realization of p–n homojunctions of a monolithic organic semiconductor single crystal by accurately controlled impurity doping .…”
mentioning
confidence: 89%
“…PYS is a suitable methodology for electronic characterization of specimens of low electric conductance [24,25], which is the case for intrinsic rubrene as a wide-gap (2.8 eV [26]) semiconductor, and particularly for detecting small modifications at the highest-occupied electronic states in an extreme sensitivity [27][28][29]. GIXD is a technique for determination of the crystal structures of thin films, and has successfully been applied to hetero-epitaxial organic semiconductor junctions built on molecular single crystals for specification of the lattice orientations [30][31][32] and even for evaluation of their crystallographic qualities by using high-resolution apparatuses [33][34][35]. It was confirmed that homoepitaxial rubrene single crystals grow without any apparent lattice distortion up to the thickness of 100 nm by the present GIXD measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Overall diffraction patterns of the sample surfaces were collected by two-dimensional (2D) GIXD measurements by using a 2D X-ray detector PILATUS300K, which was set approximately perpendicular to the incident X-ray, and crystallographic coherent lengths along in-plane directions were evaluated by high-resolution (HR) GIXD spot analyses in the 2θ directions using a NaI scintillation counter and a Ge(111) analyzer crystal. Detailed descriptions of the experimental conditions are found elsewhere [30,35]. The GIXD analyses were conducted in the ambient atmosphere.…”
Section: Methodsmentioning
confidence: 99%